BISNIS KOSMETIK DALAM ETIKA BISNIS ISLAM - Orin Oktasari (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Cosmetic Business in Islamic Business Ethics, The cosmetics business is a series of businesses in various forms of cosmetic products that are in use for improve the appearance or aroma of the human body. Business activities are muamalah activities, which Muslims in various activities must always adhere to divine norms. So in the cosmetic business activity is basically allowed according to the rules of muamalah, This is as the law of origin rather than using something is mubah, related to cosmetics, Islam does not want anything harmful to its users because something that is harmful is forbidden. But in practice cosmetics business is also a lot of cosmetics that are not feasible circulation because the substances contained in these cosmetics contain harmful ingredients have a negative impact, that is: cause effects such as irritation, the emergence of reddish spots and black spots, acne, and other health disturbances when the use of long coats such as kidney failure and some other negative impact. Business Practice as above is a mal-business practice, which contains elements of al-bathil, al-fasad, and azh-zhalim. This can cause both material and immaterial losses to my cypress, other parties or the public. The principle of honesty and openness in business is the key to success. Transparency of the consumer is when a producer is open about quality, quantity, composition, chemical elements and others so as not to harm and harm consumers. Islam prohibits free competition that justifies any means because it is against the principles of muamalah.